120k views
0 votes
What are the steps needed to solve the following problem:

(2x - 3)(x + 4) = -5?

User Shiluka
by
5.8k points

2 Answers

2 votes

These are the steps.

1. Write out the equation.

2. FInd any whole numbers and put them together and find any variables and put them together, both in parentheses.

3. Solve both equations in parentheses.

4. Divide -5 by 3 to find x. The answer is on step 5.


1. (2x - 3)(x + 4) = -5\\2. (-3 + 4)(2x + x) = -5\\3. (1)(3x) = -5\\4. 3x = -5\\5. x = -1.66

User Bastian Venthur
by
4.6k points
3 votes

Answer:

it is very simple -5 =(5)(-1)=(x+4)(2x-3).so compare( 5)=(x+4) and (x=1) it can be solved by mind.....(2x^2)+5x-7=0 then

User Idania
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.